Motyw wina we współczesnej literaturze lubuskiej = Wine motif in contemporary Lubusz literature - Meller-Rebelska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyses the influence of prose published after 1989 on Zielona Góra cultural landscape. The author studies the use of the wine theme by local writers. The methodological approach adopted here is geopoetiscs, which is a discipline that explores the relationship between literature and place.
Keywords: wino; krajobraz kulturowy; miasto; geopoetyka; Fedorowicz, Krzysztof (1970- ); Markiewicz, Czesław; wine; cultural landscape; city; geopoetics